2021
DOI: 10.3390/su131810233
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Residents’ Perception of Responsibilities for Heritage Conservation in World Heritage Buffer Zone: A Case Study of Libo Karst

Abstract: Local residents of buffer zones, as a key factor in the World Heritage conservation and sustainable development, have not received sufficient attention in most developing countries, especially in the mountainous areas where poor and backward ethnic minorities live. To fill this research gap, this paper takes the Karst World Heritage buffer zone in Libo, Guizhou Province, southwest mountainous area of China, as the research area, and explores the factors that influence the perception of residents’ responsibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The results of the study are steady with the literature (Hoang, 2021;Nilson and Thorell, 2018;Li and Han, 2021;Gulotta & Toniolo, 2019;Mason, Bohn-Spector, & Dunne Ferrone, 2000;Rypkema, Cheong, & F. Mason, 2011;Ahlfeldt et al, 2012;Lin, 2020;Goodman et al, 2021;Rubino et al, 2020;Colliers International Property Consultants Limited, 2015; Texas Private Real Property Rights Preservation Act Guidelines, Grimes [1996]; Khlaifat, 2019;Heritage Centre, 2021;Khraisat, 2017;Curtis, 1979;Fang et al, 2021;Fouad and Messallam, 2018). The literature suggests that preserving heritage buildings is crucial for maintaining cultural identity, promoting sustainable tourism, and appreciating cultural values.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The results of the study are steady with the literature (Hoang, 2021;Nilson and Thorell, 2018;Li and Han, 2021;Gulotta & Toniolo, 2019;Mason, Bohn-Spector, & Dunne Ferrone, 2000;Rypkema, Cheong, & F. Mason, 2011;Ahlfeldt et al, 2012;Lin, 2020;Goodman et al, 2021;Rubino et al, 2020;Colliers International Property Consultants Limited, 2015; Texas Private Real Property Rights Preservation Act Guidelines, Grimes [1996]; Khlaifat, 2019;Heritage Centre, 2021;Khraisat, 2017;Curtis, 1979;Fang et al, 2021;Fouad and Messallam, 2018). The literature suggests that preserving heritage buildings is crucial for maintaining cultural identity, promoting sustainable tourism, and appreciating cultural values.…”
supporting
confidence: 81%
“…While historic district designation can promote residential renovations, Curtis (1979) notes that neglecting repairs and maintenance can lead to deterioration. Fang et al (2021) found that community involvement in heritage preservation is essential and influenced by factors like environmental protection behavior and recognition of heritage value. Fouad and Messallam (2018) emphasized the importance of community involvement in the preservation of historic cities like As-Salt.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this paper, we constructed the RSEI model through the GEE platform to objectively, comprehensively, and deeply analyze the changing trends and spatial and temporal patterns of ecological environment quality in the Libo-Huanjiang karst WNHS in the past 20 years, and the study is representative and reference value. Through the comprehensive analysis results of this paper, the areas with poor and worse ecological grades of the Libo-Huanjiang heritage site are mainly concentrated in the centraleastern part of the site (figure 3), which is mainly since the area was formerly a scenic area with a relatively well-developed tourism industry [41]. The buffer zone in the area has aboriginal people who have lived here for generations.…”
Section: Discussionmentioning
confidence: 91%
“…Heritage tourism research began in the 1990s with a group of European scholars who were the first to explore the topics like heritage establishment and conservation, and gradually expanded by North American scholars who focused on natural heritage conservation and sustainable development in the context of protected areas and national park systems ( Harvey, 2008 ; Harrison et al, 2020 ; Smith, 2020 ; Gandarillas and McCall, 2021 ; Santoro et al, 2021 ). Since China joined the UNESCO World Heritage Committee, heritage research has gradually flourished and the primary studies can be summarized in the following four themes: fundamental issues of heritage sites and sustainable development ( Shen and Chou, 2021 ; Zhang and Lee, 2022 ; Zhou et al, 2022 ), heritage tourists ( Fang et al, 2021 ; Gao et al, 2021 ; Xu et al, 2022 ), benefits of heritage tourism stakeholders and heritage communities ( Chen, 2022 ; Zhang and Brown, 2022 ) and heritage tourism activities ( Zhang and Lee, 2022 ). In addition, the Chinese government and heritage conservation departments have placed strategic importance on the preservation and inheritance of cultural heritage.…”
Section: Introductionmentioning
confidence: 99%